Influence of Obesity on Pneumococcus Infection Risk in the Elderly - Frasca, Daniela; McElhaney, Janet (Frontiers in Endocrinology, 2019)
Obesity negatively affects immune function and host defense mechanisms. Obesity is associated with chronic activation of the innate immune system and consequent local and systemic inflammation which contribute to pathologic conditions such as type-2 diabetes mellitus, cancer, psoriasis, atherosclerosis and inflammatory bowel disease. Individuals with obesity have increased susceptibility to contract viral, bacterial and fungal infections and respond sub-optimally to vaccination. In this review, we summarize research findings on the effects of obesity on immune responses to respiratory tract infections (RTI), focusing on Streptococcus pneumoniae (“pneumococcus”) infection, which is a major cause of morbidity and mortality in the US, causing community-acquired infections such as pneumonia, otitis media and meningitis. We show that the risk of infection is higher in elderly individuals and also in individuals of certain ethnic groups, although in a few reports obesity has been associated with better survival of individuals admitted to hospital with pneumococcus infection, a phenomenon known as “obesity paradox”. We discuss factors that are associated with increased risk of pneumococcal infection, such as recent infection with RTI, chronic medical conditions and immunosuppressive medications.